Rak želodca - Jelenc, Franc (Zdravniški vestnik, 2003)
Background. In contrast to the incidence of esophageal cancer, the incidence of gastric cancer is decreasing in our country and worldwide. The location of gastric tumors is shifting from the distal portion of the stomach to the proximal stomach and the gastric cardia. Despite advances in surgical therapy for gastric cancer, the overall prognosis of patients with this disease has not improved markedly the past decades because, these tumors continue to be diagnosed at an advanced stage. Systemic and local recurrences are common evenafter complete tumor resection and extensive lymphadenectomy. Multidisciplinary approaches with adjuvant and neoadjuvant chemotherapy, radiotherapy, or combined radiochemotherapy is the focus of many studies. The problem is in study design, to stratified patients according to tumor location, extent of tumor, type of resection, extent of lymphadenectomy, and experience of the surgeon or institution performing the resection. Each of these factors may independently influence to prognosis of the disease. Conclusions. The most important prognostic factors in the surgical treatment ofgastric cancer and the principles of the treatment of gastric cancer are presented in this article. The results of the surgical treatment of gastric cancer from different surgical departements of Slovenian hospitals are described. The number of the patients with gastric cancer have dicreased in the past seven years. A significant improvement in the early postoperative results was not observed in the same period.
Keywords: Diagnosis; Drug Therapy; Neoplasm Staging; Novotvorba, stadij; Stomach Neoplasms; Surgery; Želodec, novotvorbe